Advanced composite materials and manufacturing engineering : selected, peer reviewed papers from the 2012 International Conference on Advanced Composite Materials and Manufacturing Engineering (CMME2012) October 13-14, 2012, Beijing, China - Xu, B.; Li, H. Y. (Trans Tech Publications, 2012)
The proceedings of the International Conference on Advanced Composite Materials and Manufacturing Engineering (CMME2012), held on the 13 and 14 th October 2012 in Beijing, China, comprise 94 peer-reviewed papers grouped into: Advanced Composite Materials and Composite Properties of Materials; Materials and Mechanics Studies in Manufacturing Engineering; Materials Engineering and Materials Application Engineering. Review from Book News Inc.: Materials scientists, manufacturing engineers, and other contributors present 93 selected and peer-reviewed papers on such topics as the synthesis and perf.
Keywords: Composite materials -- Congresses.; Production engineering -- Congresses.; elektronické knihy; electronic books